Genetics and Expression Analysis of Anthocyanin Accumulation in Curd Portion of Sicilian Purple to Facilitate Biofortification of Indian Cauliflower - Singh, Shrawan; Kalia, Pritam; Meena, Rahul Kumar; Mangal, Manisha; Islam, Sabina; Saha, Supradip; Tomar, Bhoopal S. (Frontiers in Plant Science, 2020)
The present study was undertaken to know the genetics of purple colour of cauliflower curds using a Sicilian Purple ‘PC-1’ and a white curding mid-late group genotype of Indian cauliflower. For this, a cross was attempted between ‘DC-466’ (white curd) and ‘PC-1’ (purple curd) and observed intermediate level of purple pigmentation on curds in F1 plants. Segregation of F2 population (173) revealed that the purple colour of the curd was governed by a single gene dominant over white, but the expression of trait was incomplete. It was substantiated by segregation of plants of BC1 and F2:3(intermediate) generations into 1(white):1(intermediate) and 1(white):2(intermediate):1(intense), respectively. The F2, B1 and B2 generations segregated into purple(intermediate to intense): white curding plants in the ratio of 126: 47, 26:24 and 40:0, respectively fitting well with the Mendelian ratio of single gene for purple curds. However, purple pigmentation on curds ranged from very light to intense, which corroborated with the wide range of anthocyanin content in F2 (3.81-48.21 mg/100 g fw). Out of three molecular markers from high resolution map of Pr gene in purple colour cauliflower ‘Graffiti’, only BoMYB3 marker could distinguish purple and white curding parents but did not show co-segregation while investigated in F2 population. Expression of BoMYB1 gene was up regulated in both the purple curd genotypes ‘PC-1’ and ‘Graffiti’ in comparison to white curded ‘DC-466’, while BoMYB2 gene was slightly upregulated in ‘PC-1’ but down regulated in ‘Graffiti’. Occurrence of ‘Broccoli type’ F2 individuals and their genetic stability in F2:3 support the intermediate position of ‘Sicilian Purple’ between broccoli (Calabrese) and cauliflower. There was not any correlation between curd colouration and pigmentation on apical leaf and stem portion, indicating difference of expression in ‘PC-1’ than ‘Graffiti’. The information obtained is useful for breeding anthocyanin rich attractive purple curding ‘specialty cauliflower’ for better consumer health and growers’ earnings.